Evaluation of ultra wideband indoor localization with trilateration and min-max techniques - Monta, Suppachai; Promwong, Sathaporn; Kingsakda, Vongkeo (My University, 2016)
UWB indoor localization has been extensively researched because of its various applications. It can be used in firefighters tracking, logistics and military service. This system requires high accuracy in an indoor environment. In this paper the comparison between trilateration and min-max localization techniques using received signal strength (RSS) and time of arrival (TOA) parameters. This study based on the indoor localization using ultra wideband (UWB) transmission model. The vector network analyzer (VNA) was used to measure at the frequency ranging from 3 GHz to 11 GHz. The biconical antennas were used as both transmitter (Tx) and receiver (Rx) antennas. The accuracy and precision are also studies in the term of distance error. The cumulative distribution function (CDF) of distance error of each case is shown. From the results, the trilateration technique using TOA parameter has the most accuracy.
Keywords: min-max technique; RSS; TOA; trilateration technique; UWB localization